Alarm or rather false alarm? A literature review of empirical research studies into financial speculation with agricultural commodities - Thomas Glauben; Ingo Pies; Sören Prehn; Matthias Georg Will (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2012)
An evaluation of 35 research papers into the impact of financial speculation on agricultural commodities markets has revealed: The vast majority of studies did not confirm the concerns that prevail in public discourse. The current state of knowledge indicates only a few, and weak, findings that verify the assumption that the rise in financial speculation in recent years has increased (1) the level or (2) the volatility of agricultural commodity prices. Instead, those developments have rather been caused by fundamental factors in the real economy. This is why the majority of academic studies are not in favor but against (3) enacting regulatory barriers to market entry. Transaction taxes or position limits are described as involving high risks. Various studies explicitly warn against overregulation, which would impair rather than improve the functionality of agricultural markets. Seen in this light, the alarmism about financial speculation should be classified as a false alarm: Those who desire to effectively combat hunger in the world have to take real-economy precautions to ensure that food supplies will match the envisaged increasing demands. – – Eine Auswertung von 35 Forschungsarbeiten über den Einfluss der Finanzspekulation auf die Agrarrohstoffmärkte gelangt zu folgenden Ergebnissen: Die weit überwiegende Mehrheit der Studien kann die in der öffentlichen Diskussion vorherrschenden Befürchtungen nicht bestätigen. Gemäß aktuellem Erkenntnisstand sprechen nur wenige und zudem schwache Befunde für die Auffassung, dass die Zunahme der Finanzspekulation in den letzten Jahren (1) das Niveau bzw. (2) die Volatilität der Preise für Agrarrohstoffe hat ansteigen lassen. Hierfür waren vielmehr realwirtschaftliche Faktoren verantwortlich. Deshalb sind die wissenschaftlichen Studien mehrheitlich nicht dafür, sondern dagegen, (3) regulatorische Marktzutrittsbarrieren zu errichten. Transaktionssteuern oder Positionslimits werden als sehr riskant angesehen. Zahlreiche Studien warnen explizit vor einer Überregulierung, die die Agrarmärkte nicht besser, sondern schlechter funktionieren lassen würde. Insofern ist der Alarm zur Finanzspekulation als Fehl-Alarm einzustufen: Wer den Hunger in der Welt wirksam bekämpfen will, muss realwirtschaftlich dafür Sorge tragen, dass das Angebot an Nahrungsmitteln mit der auf absehbare Zeit steigenden Nachfrage Schritt halten kann.
urn:nbn:de:gbv:3:2-32074
Keywords: 330